Effective marginal tax rates for US investors in Germany and Europe : an analysis of recent tax reforms in Germany - Christoph Spengel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
In this paper the impact of the corporate tax systems of the 15 EU-member states on the investment and the financing decision of an US multinational corporation is analysed. The calculation of the resulting effective marginal tax rates (EMTR) closely follow the model of King and Fullerton. There is not only a great variation among the EMTR in the EU-member states which can affect cross-border location, investment and financing decisions. Moreover, recent reform proposals in Germany are likely to have an impact both on investment patterns and financing decisions of US multinationals in Germany.
Keywords: 330; Tax burden comparison; capital income taxation; tax competition; tax harmonization in Europe; cross-border tax planing; Unternehmensbesteuerung; Kapitalertragsteuer; Steuerbelastung; Multinationales Unternehmen; Steuerplanung; Direktinvestition; USA; Deutschland; EU-Staaten; Steuerreform